PENGARUH MODEL FLIPPED CLASSROOM BERBANTUAN MEDIA INTERAKTIF KAHOOT TERHADAP HASIL BELAJAR DAN KEMANDIRIAN SISWA DALAM PEMBELAJARAN MATEMATIKA MATERI PECAHAN KELAS IV MI TAHFIDZ DAN BAHASA AN-NUR TAHUN PELAJARAN 2025/2026 - Khusnul Khotimah; Supriyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes and learning independence of students in mathematics learning on fraction material in Grade IV at MI Tahfidz Dan Bahasa An-Nur. Learning activities that were still teacher-centered caused students to be less active and have low motivation for independent learning. This study aimed to determine the effect of the Flipped Classroom model assisted by Kahoot interactive media on students’ learning outcomes and learning independence in learning mathematics on fraction material for Grade IV students. This research used a quantitative approach with a quasi-experimental research type and a nonequivalent control group design. The population of this study consisted of all Grade IV students totaling 30 students, who had already been divided into classes, so that Class A became the experimental group (n=15) and Class B became the control group (n=15). Data collection techniques included learning outcome tests, learning independence questionnaires, observation, and documentation. Data analysis was conducted through normality tests, homogeneity tests, and MANOVA tests. The results of the study showed that there was a significant effect of the Flipped Classroom model assisted by Kahoot on mathematics learning outcomes, with a significance value of 0.000 < 0.05. In addition, there was also a significant effect on students’ learning independence, with a significance value of 0.000 < 0.05. Simultaneously, the Flipped Classroom model assisted by Kahoot also had a significant effect on both learning outcomes and students’ learning independence, with a Pillai’s Trace value of 0.891 and a significance value of 0.000. Therefore, the Flipped Classroom model assisted by Kahoot was proven effective in improving students’ learning outcomes and learning independence on fraction material.